The genus Microhyla (Anura: Microhylidae) in Pakistan: species status and origins - Jablonski, Daniel; Khan, Muazzam Ali; Masroor, Rafaqat (Zootaxa, 2020)
The territory of Pakistan has been influenced by biota from different geographic directions, and is divided zoogeographically into the Palearctic and Oriental regions (Khan 2006; Masroor 2012). This makes Pakistan one of the important territories in Eurasia in the understanding of past biodiversity dynamics. Well-known examples of Oriental elements among its amphibian fauna are observed in all four families of toads and frogs currently known from Pakistan: Bufonidae, Microhylidae, Megophryidae, and Dicroglossidae. In this short contribution, we focused on the species status and the origins of the genus Microhyla (Microhylidae), known from the north-eastern part (Punjab, Islamabad, and Azad Jammu and Kashmir; Masroor 2012) of the country. However, Sarkar (1984), also reported Microhyla from Bhuj in Gujarat, India, very close to the southern Pakistani province of Sindh. This genus has not yet been reported from the Palearctic region of the country and all currently known localities are from the Oriental parts of Pakistan (i.e. eastward of the Indus River). The genus is represented in the country by M. ornata (Duméril & Bibron, 1841), originally reported as Oxyglossus lima (Khan 1968). However, in view of the overall distribution and diversity of the genus based on genetic data (Garg et al. 2018, 2019; Gorin et al. 2020), it appears that populations from Pakistan could possibly have a different evolutionary history and be different taxon (see the currently scattered range of the genus between northern and western India and Pakistan; Fig. 1). Therefore, we tested this assumption using mitochondrial (mt) and nuclear (n) DNA data.